Nonclinical aspects of venous thrombosis in pregnancy. Issue 3 (25th September 2015) - Struble, Evi; Harrouk, Wafa; DeFelice, Albert; Tesfamariam, Belay
Abstract : Pregnancy is a hypercoagulable state which carries an excess risk of maternal venous thrombosis. Endothelial injury, alterations in blood flow and activation of the coagulation pathway are proposed to contribute to the hypercoagulability. The risk for thrombosis may be accentuated by certain drugs and device implants that directly or indirectly affect the coagulation pathway. To help ensure that these interventions do not result in adverse maternal or fetal outcomes during pregnancy, gravid experimental animals can be exposed to such treatments at various stages of gestation and over a dosage range that would identify hazards and inform risk assessment. Circulating soluble biomarkers can also be evaluated for enhancing the assessment of any increased risk of venous thrombosis during pregnancy. In addition to traditional in vivo animal testing, efforts are under way to incorporate reliable non‐animal methods in the assessment of embryofetal toxicity and thrombogenic effects. This review summarizes hemostatic balance during pregnancy in animal species, embryofetal development, biomarkers of venous thrombosis, and alterations caused by drug‐induced venous thrombosis. Birth Defects Research (Part C) 105:190–200, 2015. © 2015 Wiley Periodicals, Inc.